The research of professional ethics of tax auditor seeking the trust in tax - Giriūnienė, Gintarė (Buhalterinės apskaitos teorija ir praktika, 2014)
In today's economy, the subject of taxation, in particular, precise calculation and evaluation of taxes is becoming more and more relevant. There is a practice, where tax auditors performing audits of the business entity often do not even know whether it is ethical to allow the business entity, i.e. taxpayer, to correct some of the errors appearing in the tax records, and not to punish the business by fines and interests, as is prescribed by the Law of Tax Administration of the Republic of Lithuania. It should be noted that there was a similar problem several decades ago among accountants and this led to the emergence of professional codes of ethics of accountants. The discussions of the behaviour of the tax auditor, auditing one or another company, in the context of professional ethics, what fundamental values and principles should he be guided by in order to maintain good quality of work, following the relevant moral norms, enables the argument that the topic of tax auditor's assessment in the context of professional ethics has not been analysed thoroughly enough, therefore the identification of tax auditor's ethical norms, values, principles and, most importantly, assessment is extremely important for the purpose of making the individual tax auditor’s , as well as all the tax system’s performance more efficient. Even for a very knowledgeable in his field tax auditor it is no easy to tell what kind of personal traits suggest that certain behaviour is ethical, consequently the article analyses the main values and principles of professional ethics, that should serve as guidelines not only for tax auditors, but also for any other person, seeking higher results in his profession. Therefore the objective of the research is to conduct a research on tax auditors’ professional ethics.The code of ethics plays a special role in the evaluation of professional ethics; it defines the core values and principles for ethical behaviour. A tax auditor, seeking professional growth through quality performance, taking into account the moral obligations, should not only comply with the fundamental values, such as honesty, objectivity, impartiality, confidentiality and sense of duty, but also provide a decent example for the audited company’s employees to demonstrate the integrity of the entire tax system and thus create confidence in the Lithuanian tax system. The results of a questionnaire survey showed that the tax auditor's professional ethics are directly connected with the taxpayer's trust in the Lithuanian tax system. Therefore, the existing practice of different taxpayers committing identical offences and being treated differently undermines the confidence not only in tax auditors and their professional ethics, but also in the tax system of the country as a whole. The questionnaire survey results suggest that, according to the taxpayers, it is essential for the tax auditor to follow such principles at work as impartiality, confidentiality and thoroughness. All of the above should be included in the tax auditor's code of ethics.
Keywords: tax auditor; professional ethics; principles of professional ethics